Autophagy Is Required for Strawberry Fruit Ripening - Sánchez-Sevilla, José F.; Botella, Miguel A.; Valpuesta, Victoriano; Sanchez-Vera, Victoria (Frontiers in Plant Science, 2021)
Autophagy is a catabolic and recycling pathway to maintain cellular homeostasis under normal growth and stress conditions. Two major types of autophagy, microautophagy and macroautophagy, have been described in plants. During macroautophagy, cellular content is engulfed by a double-membrane vesicle called autophagosome. This vesicle fuses its outer membrane with the tonoplast and releases the contents into the vacuole for degradation. During certain developmental processes, autophagy is enhanced by induction of several autophagy-related genes (ATG genes). Autophagy in crop development has been studied in relation to leaf senescence, seed and reproductive development and vascular formation. However, its role in fruit ripening has been only partially addressed. Strawberry is an important berry crop, representative of non-climacteric fruit. We have analyzed the occurrence of autophagy in developing and ripening fruits of the cultivated strawberry. Our data show that most ATG genes are conserved in the genome of the cultivated strawberry Fragaria x ananassa and they are differentially expressed along the ripening of the fruit receptacle. ATG8-lipidation analysis proves the presence of two autophagic waves during ripening. Besides, we have confirmed the presence of autophagy at the cellular level by the identification of autophagic related structures at different stages of the strawberry ripening. Finally, we show that blocking autophagy either biochemically or genetically dramatically affects strawberry growth and ripening. Our data support that autophagy is an active and essential process with different implication during strawberry fruit ripening.